Green business strategy and ecoinnovation in manufacturing companies; effects on environmental performance - Castillo Esparza, Ma. Mónica Gloria Clara; Maldonado Guzmán, Gonzalo; Montejano García, Salomón; Mejía Trejo, Juan (Cuadernos de Administración, 2024)
In response to an increasing responsibility to safeguard the environment, the business world has developed strategies and innovations that mitigate the harmful effects of its activities. The Green Business Strategy (GBS) emerges as an imperative need to address such effects, with eco-innovation collaborating to achieve environmental goals. The present empirical and cross-sectional research asserts that GBS maintains significant relationships on types of ecoinnovation, encompassing products, processes, and organizational practices, contributing to enhanced environmental performance for Mexican manufacturing companies. A survey was administered to 300 managers within the manufacturing sector with a Likert scale. The collected data was analyzed using structural equations and the SMART PLS-SEM program. The results reveal a significant impact of the GBS on eco-innovations in products, processes, and the organization, as well as on environmental performance. While process eco-innovation significantly influences environmental performance, product and organizational eco-innovation do not demonstrate a similar impact. Additionally, eco-innovation in processes mediates the relationship between GBS and environmental performance. This study highlights the pivotal role of GBS as a facilitator of eco-innovation practices in the manufacturing sector. In addition, its implementation contributes to protecting and caring for the environment. Therefore, decision-makers within companies and governmental bodies are encouraged to support and promote the adoption of GBS and eco-innovation.